Animal Drag: The Critical and Conscious Performance of Animality - McCartney, Nicola (Humanimalia, 2024)
This essay proposes Animal Drag as an activist performance in which a human critically and consciously performs animality to de-centre the human. Dress and adornment are key to its dissidence. Animal Drag’s potential is demonstrated through an analysis of Terry Notary’s performance of a nonhuman primate within Ruben Östlund’s 2017 film The Square. Drawing on posthuman studies, scholarship on subordinated groups and from the field of animal studies, the reading of this performance shows how Animal Drag inherently queers humanist and essentialist notions of classification, particularly the human / animal divide. Paying homage to drag, the essay demonstrates how the material and social semiotics of performance can render transparent the constructions of race, coloniality, ability, and gender, as much as species — in other words, “doing human”. Through theories of dress and prosthesis, highlighting how techne facilitates in-between and “becoming” states, and affect theory, this article argues that humans and nonhumans might share vulnerabilities via Animal Drag. Culture is understood through language and dress, which have been mobilised to construct Otherness. As such, this essay posits that Animal Drag should take place within capitalist Culture industries, as both weapons and targets, to undress powers present and performed. Animal Drag is offered as both practice and theory, content and form.